Assessment of Nutritional Status and Growth in Children with End Stage Renal Disease Undergoing Maintenance Hemodialysis: A Multicenter Study - Zina Rashid; Besmah Ali; Nariman Azat (The Iraqi Journal of Medical Sciences, 2023)
Background: Chronic kidney disease is a worldwide health problem, with increasing prevalence and adverse outcomes. Children's nutritional status reflects the degree to which physiologic needs for nutrients are being met. Impairment of growth is associated with all stages of chronic renal failure Objective: To assess the nutritional status and the severity of malnutrition in children undergoing hemodialysis (HD) in all pediatrics dialysis centers in Baghdad. Methods: A total of 86 participants (41 males and 45 females), with end stage renal disease (ESRD) undergoing HD, from all pediatric HD centers in Baghdad City, recruited in this cross-sectional study with analytic components, among six months’ period. A structured interview questionnaire was used with the children or their care givers, included: demographic and clinical characteristics of patients, nutritional assessment of studied children using pediatric subjective global nutritional assessment (SGNA) tool and also growth parameters to assess the growth status of the study group. Results: The overall proportion of estimated nutritional status was as follow: Thirty-three children (38.4%) were normal/well nourished, 39 patients (45.3%) were moderately malnourished and 14 patients (16.3%) were severely malnourished. Uremic symptoms were more significantly associated with severe state of nutritional deficiency (p=0.002). The duration of dialysis was significantly higher in children with severe nutritional deficiency in comparison with children with normal or moderate nutritional deficiency, their mean and interquartile range were 41.00 (76.00) months versus 24.00 (27.00) months and 24.00 (38.00) months, respectively (p = 0.001). Conclusion: Nutritional assessments are complex and critical in pediatric patients with ESRD. Using a comprehensive tool such as pediatric SGNA is more reflective of their nutritional status than when compared to other parameters. Keywords: Nutritional status, pediatrics end stage renal disease, pediatrics subjective global nutritional assessment (SGNA) Citation: Rashid ZA, Ali BM, Azat NFA. Assessment of nutritional status and growth in children with end stage renal disease undergoing maintenance hemodialysis: A multicenter study. Iraqi JMS. 2023; 21(1): 71-80. doi: 10.22578/IJMS.21.1.7